Building a bulletproof whistleblowing environment: an accountant’s perspective - Shanmugavel Rajeevan (Emerald Publishing Limited, 2019)
The purpose of this paper is to assess the appropriateness of the factors that contribute to building a better whistleblowing environment and culture within an organisation and provide guidelines on how to build a better whistleblowing environment within an organisation.In total, 592 questionnaires were circulated to 148 accounting firms licensed to carry out statutory audits of public limited companies expecting responses from 4 stakeholders from each entity. Out of the 592 questionnaires, only 148 questionnaires were usable, representing a 25 per cent overall response rate.It is recommended to encourage a proactive whistleblowing environment by encouraging whistleblowing culture among employees of the organisations. However, there is disagreement among the respondents for some of the selected components that contribute to building a better whistleblowing environment and culture within an organisation.The findings of this study can be used by the management of the organisations to identify frail areas of whistleblowing initiatives within the organisation and take remedial actions rectify the issues. Authorities can use the findings of the study to implement or amend the existing rules and regulations to encourage whistleblowing.This study in contrast to the existing studies on determinants of whistleblowing attributes, provides knowledge on developing components/guidelines to encourage whistleblowing attributes and culture.